Automobile museum and assembly plant: Pragoti industries ltd. Barabkunda, Chittagong - Chowdhury, Tanzir Taher (BRAC University, 2011)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2011.